Will covid-19 vaccines save lives? Current trials aren't designed to tell us. (21st October 2020) - Doshi, Peter
Abstract : The world has bet the farm on vaccines as the solution to the pandemic, but the trials are not focused on answering the questions many might assume they are. Peter Doshi reports